Modelling of Social Key Performance Indicators of Corporate Sustainability Performance - Marie Pavláková Dočekalová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
Corporate social performance is discussed in this paper. The aim of this article is to propose indicators of social performance in the context of corporate sustainability. Relevance of the proposal has been verified through a questionnaire that focused on large manufacturing companies in the Czech Republic. Using statistical methods, it was found that a basic set of sixteen indicators can be replaced by six key performance indicators – Percentage of employees covered by collective agreement, Wage discrimination, Occupational diseases, Violations of ethical code, Expenditures on identifying and ensuring customer satisfaction and Percentage of products and services assessed for their influence on health and safety of customers. These results aim to contribute to both academy and corporate practitioners, who want to improve corporate social performance and through the use of key performance indicators to support transparency and sustainability of their business. This study, however, has some limitations. The key performance indicators are designed specifically for large manufacturing companies of group 27.1 CZ‑NACE.